ANALISIS BEBAN KERJA KARYAWAN PADA ADMINISTRASI DAN WORK PLANNER DIVISI PAP 1 PT. IKPP - Dedi Dermawan (Research Center University of Pahlawan Tuanku Tambusai, 2021)
PT. Indah Kiat Pulp & Paper is one of the subsidiaries under the Sinarmas Group that the led is Mr. Eka Tjipta Wijaya. The company is a manufacturing company engaged in pulp and paper production. The company location is located at Jl. Raya Perawang - Minas km 26, Desa Pinang Sebatang kec. Tualang district. Siak, Riau Province. PT. IKPP has 106 divisions and 284 sections in its work environment, such as the PAP 1 division, there are 4 units/sections of paper production, including Paper Machine 1 which has 64 employees, Paper Machine 5 has 56 employees, Paper Machine 7 has 73 employees. people, and Paper Machine 8 which has 51 employees working in the field. In each unit/section there is 1 Administration employee and 1 Work Planner employee who takes care of all office administration, sometimes there are employees who are not the same workload so that one employee is unemployed, and the other employee is busy doing piling up work. This makes researchers want to know-how with the workload owned by each employee in this case Administration and Work Planner and changes the workload hours to the number of people needed to complete the work with the FTE (Full Time Equivalent) method. This method can provide information about how heavy the workload of someone who can be categorized into normal, overload, or underload of work from the Administration and work planner and can calculate the number of employees to complete the work based on their FTE value.